THE IMPACT OF TRIPS AGREEMENT ON ACCESS TO MEDICINES IN DEVELOPING COUNTRIES: LEGAL CHALLENGES FACED BY THE PHARMACEUTICAL INDUSTRY PARTICULARLY IN INDIA (UUM Journal of Legal Studies, 2012)
The impact of intellectual property rights in particular patent relating to public health has posed numerous challenges faced by developing countries who are members of World Trade Organisation (WTO). This paper examines the impact of TRIPS Agreement (Trade Related Intellectual Property Rights) in relation to developing countries in general with specification made to India. Significant changes brought about by the TRIPS flexibilities in particular usage of compulsory licensing and Bolar provision have to a certain extent benefited the developing countries in the field of public health during national emergency. The TRIPS flexibilities by way of amendment have helped countries that (do not possess manufacturing capacities) to import medicines. Some developing countries even utilised TRIPS flexibilities in an aggressive manner to enforce their right to have access to medicines from other countries for the benefit of their citizens. Further, TRIPs flexibilities have helped developing countries to manufacture generic products to make it affordable to the people. This paper specifically examines the impact of the TRIPS Agreement on Indian generic pharmaceutical industry and the legal challenges faced by Indian pharmaceutical industry after the implementation of product patent regime effective from 1 January 2005. The Patent Amendment Act 2005(India) will be looked into especially on the controversy in respect of Section 3(d) of the Patent Amendment Act 2005(India) on the requirement of patentability. The new Section 92A of the Patent Amendment Act 2005(India) on the grounds to invoke compulsory licensing will be analysed to see whether Indian government has applied restrictive or broad approach, as compulsory licensing is certainly an important legal